2020
DOI: 10.1371/journal.pone.0241376
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution of journalistic attention for scientific studies and scientific sources: An input–output analysis

Abstract: Based on the decision-theoretical conditions underlying the selection of events for news coverage in science journalism, this article uses a novel input-output analysis to investigate which of the more than eight million scientific study results published between August 2014 and July 2018 have been selected by global journalism to a relevant degree. We are interested in two different structures in the media coverage of scientific results. Firstly, the structure of sources that journalists use, i.e. scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…In a previous study, we have shown that the specific conditions and selection criteria in the journalistic coverage of new scientific results lead to an uneven frequency distribution of selected studies and journals (Lehmkuhl & Promies, 2020). In line with the argumentation of Esser's model of sociological explanation (1999), we assume that this social structure of congruent choice on the macro-level, i.e.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…In a previous study, we have shown that the specific conditions and selection criteria in the journalistic coverage of new scientific results lead to an uneven frequency distribution of selected studies and journals (Lehmkuhl & Promies, 2020). In line with the argumentation of Esser's model of sociological explanation (1999), we assume that this social structure of congruent choice on the macro-level, i.e.…”
Section: Introductionmentioning
confidence: 68%
“…Studies by Suleski and Ibaraki (2010) and Kiernan (2016) also showed the dominance of just a few journals in the media coverage of scientific results. Lehmkuhl and Promies (2020) have summarized all studies which analyzed science journalists' preferred sources. They discovered that journalistic coverage of scientific results is primarily based on the journals Nature, Science, New England Journal of Medicine (NEJM), The Lancet, and the Journal of the American Medical Association.…”
Section: The Logic Of Selectionmentioning
confidence: 99%
See 3 more Smart Citations